2007
DOI: 10.1007/s10792-007-9123-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of macular status in recent-onset branch retinal vein occlusion: an optical coherence tomography study

Abstract: OCT delineates macular changes at a stage when fundus biomicroscopy and fluorescein angiography are not very informative. The anatomical cause for the increase in MT i.e., SRD and/or CME is also well delineated. Non-ischemic maculae show an early and more rapid decline in MT compared with ischemic occlusions. An increase in MT at 3 months on OCT in BRVO patients could be an indication of a possible ischemic course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 11 publications
2
34
1
Order By: Relevance
“…Macular edema may develop in 5–15% of eyes over a 1-year period [69]. Another study reported an incidence of 15% at 7.5 months following the onset of BRVO [72]. Of eyes with macular edema at presentation, 18% achieved resolution by 4.5 months, and 41% by 7.5 months.…”
Section: Natural History Of Rvomentioning
confidence: 99%
“…Macular edema may develop in 5–15% of eyes over a 1-year period [69]. Another study reported an incidence of 15% at 7.5 months following the onset of BRVO [72]. Of eyes with macular edema at presentation, 18% achieved resolution by 4.5 months, and 41% by 7.5 months.…”
Section: Natural History Of Rvomentioning
confidence: 99%
“…(6,7) Most common cause in decrease in visual acuity was cystoid changes at macula and macular ischaemia, which was confirmed by fundus fluorescein angiography. (8,9) None of the patients in our series developed retinal neovascularisation or iris neovascularisation, which could be due to small sample size of the study and less incidence of neovascularisation in BRVO as compared to CRVO (Central retinal vein occlusion).…”
Section: Resultsmentioning
confidence: 92%
“…In BRVO patients, SRD occurs as a result of transudation of extracellular fluid into the subretinal space with the site of detachment being determined by foveal architecture, particularly the presence of the Müller cell cone (21,22) . Furthermore, when the barrier function of the ELM breaks down due to traction on the Müller cell cone, intraretinal fluid moves into the subretinal space resulting in an increase of SRD and alleviation of retinal edema (12,15) .…”
Section: Discussionmentioning
confidence: 99%